Method for preparing titanium dioxide nanotube on surface of titanium or titanium alloy
By using fluorine-free electrolyte and bioacid chemical polishing liquid on the surface of titanium or titanium alloys, adjusting the electrolyte composition and anodizing parameters, the environmental and safety problems of fluoride electrolyte are solved, and the uniformity of titanium dioxide nanotubes is improved and Integrity reduces production costs.
Patent Information
- Application Number
- CN202411110361.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-13
AI Technical Summary
The use of fluoride electrolyte in the existing titanium dioxide nanotube preparation methods poses environmental and safety risks, and is prone to nanotube defects and affects performance.
Using fluorine-free electrolyte and bioacid chemical polishing liquid, by adjusting the electrolyte composition and anodizing parameters, using sodium dodecylbenzenesulfonate and 5-aminobenzotriazole and other components to form a stable electrolyte interface and improve nanometers. Tube growth to avoid defects.
It reduces environmental pollution and safety risks, reduces production costs, significantly improves the uniformity and integrity of nanotubes, and enhances its dispersion and binding power in aqueous media.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of titanium dioxide nanotube preparation, in particular to a method for preparing titanium dioxide nanotubes on an alloy surface. Background Art
[0002] Titanium dioxide nanotubes are one-dimensional nanostructured materials. This nanostructure has biocompatibility, high specific surface area, photocatalytic activity, photoelectric properties, and porosity, which makes it widely used in many fields. Titanium dioxide nanotubes show good biocompatibility, making them potential uses in biomedical fields such as drug delivery systems, tissue engineering, and biosensors.
[0003] Titanium dioxide nanotubes are most commonly prepared by anodization, in which titanium metal is oxidized in an electrolyte to form nanotube arrays. Preparing titanium dioxide nanotubes with uniform pore size and vertical orientation is the key to maximizing their performance in various applications. Uniform pore size ensures the consistency and predictability of the material, which is particularly important in the fields of catalysis, photoelectric conversion, biomedical applications, etc.
[0004] By controlling the parameters of the anodization process, such as using an electrolyte containing a specific concentration of acid or salt, such as phosphoric acid, oxalic acid, sulfuric acid and fluoride, it can help control the pore size, or by voltage control, temperature management, time adjustment, etc., the uniformity and pore size of the nanotubes can be directly affected. Vertically aligned nanotubes can be formed on a titanium substrate by applying voltage to titanium metal in a suitable electrolyte, which usually contains fluoride ions, such as HF, which help etch the titanium surface and promote the growth of nanotubes.
[0005] However, electrolytes such as solutions containing hydrofluoric acid (HF) can promote the formation of nanotubes, but HF is a highly corrosive and toxic chemical that poses risks to the environment and operator safety. In addition, waste disposal after HF treatment is also an environmental issue. Moreover, ordinary electrolytes may cause defects in nanotubes, such as cracks or irregular morphology, which may reduce the performance of nanotubes, especially in applications that require highly ordered and defect-free structures. Therefore, it is necessary to design a method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloys. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy, the method comprising the following steps: Using a titanium sheet or titanium alloy sheet that has been polished, cleaned, and chemically polished as an anode, anodizing is performed in a fluorine-free electrolyte, and the anodized titanium dioxide nanotubes are rinsed 2-3 times with deionized water, and dried in air to obtain a finished product with titanium dioxide nanotubes grown on the surface of the titanium sheet or titanium alloy sheet; The fluorine-free electrolyte comprises phosphoric acid, a surfactant, a solvent, a film-forming additive, a corrosion inhibitor and deionized water. In parts by mass, the mass parts of each component in the electrolyte are: 1-5 parts of phosphoric acid, 1-2 parts of surfactant, 40-60 parts of solvent, 1-2 parts of film-forming additive, 2-4 parts of corrosion inhibitor and 40-50 parts of deionized water.
[0008] The surfactant is sodium dodecylbenzene sulfonate.
[0009] The film-forming additive is vinylene carbonate.
[0010] The solvent is ethylene glycol or glycerol.
[0011] The corrosion inhibitor is 5-aminobenzotriazole and imidazole, and the mass ratio of 5-aminobenzotriazole to imidazole is 3-5:1; The preparation method of the 5-aminobenzotriazole comprises the following steps: Step 1: Synthesis of 5-nitrobenzotriazole In an ice bath, concentrated sulfuric acid is cooled to 0°C; under continuous stirring, concentrated nitric acid is slowly added to the concentrated sulfuric acid, the temperature is controlled not to exceed 10°C, and pre-cooled benzotriazole is slowly added to the mixed acid, while maintaining the reaction temperature at 10°C; the mixture is stirred at low temperature for nitration reaction, and 5-nitrobenzotriazole is obtained after neutralization and washing; Step 2: Reduction of 5-nitrobenzotriazole to obtain 5-aminobenzotriazole The 5-nitrobenzotriazole obtained in the first step is dissolved in water and heated to 50° C. Under continuous stirring, a reducing agent hydrazine hydrate solution is slowly added dropwise, the temperature is maintained at 80° C., and the addition is completed within 0.3 hours. After the addition is completed, the reaction is continued at the same temperature for 1-3 hours, the reaction mixture is cooled to 40° C., and then filtered to collect the solid product, and purified by recrystallization to obtain pure 5-aminobenzotriazole.
[0012] The voltage of the anodization is 40-70V, the temperature is 15-25°C, and the time is 10-40min.
[0013] After grinding, cleaning and chemical polishing, the thickness of the titanium sheet or titanium alloy sheet is 1-3 mm. The graphite electrode is used as the cathode, and the two electrodes are immersed in the same fluorine-free electrolyte.
[0014] The cleaning is carried out by using ultrapure water, acetone and ethanol in sequence under ultrasonic conditions for 10-20 minutes respectively.
[0015] The current density of the chemical polishing is 15-35A / dm 2 , polishing time 5-20min.
[0016] The chemical polishing solution comprises, by parts by mass: 300-600 parts of anhydrous ethanol; Malic acid 200-400 parts; Tartaric acid 200-400 parts; Perchloric acid 50-300 parts; Perchlorate 1-10 parts.
[0017] The perchlorate is one of ammonium perchlorate, sodium perchlorate and potassium perchlorate.
[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The fluorine-free electrolyte of the present application does not contain fluorine element, and fluorine element is not used in the early chemical polishing process, thereby avoiding the use of such substances and reducing potential ecological risks and environmental pollution throughout the life cycle.
[0019] 2. Some fluoride raw materials are expensive, and the fluorine-free electrolyte of the present application uses materials with lower costs, thereby reducing production costs.
[0020] 3. By adjusting the composition of the electrolyte, the defects of titanium dioxide nanotubes in electrochemical applications can be effectively overcome. Among them, sodium dodecylbenzene sulfonate can be adsorbed on the surface of nanomaterials through electrostatic interaction to form a hydrophilic shell layer, thereby preventing nanoparticles from agglomerating, improving their dispersibility in aqueous media, reducing surface defects and enhancing wettability, and significantly reducing the defects of titanium dioxide nanotubes. Vinylene carbonate can form a stable solid electrolyte interface (SEI) film on the electrode surface, protecting the electrode from further electrolyte decomposition, while reducing the dissolution and side reactions of electrode materials.
[0021] 4. Malic acid and tartaric acid used in the chemical polishing of this application are bio-based acids. Due to their biodegradability, low toxicity and good polishing effect, they can not only be used for metal polishing, but also due to their mild nature, they can reduce the impact on the environment and the safety risks to operators.
[0022] 5. Chemical polishing is a metal surface treatment process that uses chemical reactions to remove uneven parts of the metal surface to achieve a smooth and shiny effect. Traditional chemical polishing liquids usually contain highly corrosive chemicals such as hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid. Although these chemicals can be used for efficient polishing, they also bring environmental pollution and safety issues. The chemical polishing method of the present application can avoid the use of hydrofluoric acid in the anodizing pretreatment process, and also avoids the use of toxic substances such as methanol, ethers and glacial acetic acid, and will not produce volatile substances that are harmful to the human body and strong irritating odors.
[0023] 6. The corrosion inhibitor can control the growth of nanotubes, ensure that the titanium dioxide nanotubes are uniform and dense, and avoid being too thick or too thin locally. It can also improve the quality of nanotubes: making the nanotubes have better binding force and integrity. Introducing amino groups on the benzotriazole ring can change its electron cloud density, affect its interaction with the metal surface, and thus change the corrosion inhibition performance. In this application, 5-aminobenzotriazole is used in combination with imidazole, and the corrosion inhibition efficiency can be significantly improved through the synergistic effect of the two compounds. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1 A method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy, the method comprising the following steps: Using a titanium sheet or titanium alloy sheet that has been polished, cleaned, and chemically polished as an anode, anodizing is performed in a fluorine-free electrolyte, and the anodized titanium dioxide nanotubes are rinsed 2-3 times with deionized water, and dried in air to obtain a finished product with titanium dioxide nanotubes grown on the surface of the titanium sheet or titanium alloy sheet; The fluorine-free electrolyte comprises phosphoric acid, a surfactant, a solvent, a film-forming additive, a corrosion inhibitor and deionized water. The mass parts of each component in the electrolyte are: 5 parts of phosphoric acid, 1.5 parts of surfactant, 40 parts of solvent, 2 parts of film-forming additive, 2 parts of corrosion inhibitor, and 45 parts of deionized water.
[0026] The surfactant is sodium dodecylbenzene sulfonate.
[0027] The film-forming additive is vinylene carbonate.
[0028] The solvent is ethylene glycol.
[0029] The corrosion inhibitor is 5-aminobenzotriazole and imidazole, and the mass ratio of 5-aminobenzotriazole to imidazole is 3:1; The preparation method of the 5-aminobenzotriazole comprises the following steps: Step 1: Synthesis of 5-nitrobenzotriazole In an ice bath, concentrated sulfuric acid is cooled to 0°C; under continuous stirring, concentrated nitric acid is slowly added to the concentrated sulfuric acid, the temperature is controlled not to exceed 10°C, and pre-cooled benzotriazole is slowly added to the mixed acid, while maintaining the reaction temperature at 10°C; the mixture is stirred at low temperature for nitration reaction, and 5-nitrobenzotriazole is obtained after neutralization and washing; Step 2: Reduction of 5-nitrobenzotriazole to obtain 5-aminobenzotriazole The 5-nitrobenzotriazole obtained in the first step is dissolved in water and heated to 50° C. Under continuous stirring, a reducing agent hydrazine hydrate solution is slowly added dropwise, the temperature is maintained at 80° C., and the addition is completed within 0.3 hours. After the addition is completed, the reaction is continued at the same temperature for 1-3 hours, the reaction mixture is cooled to 40° C., and then filtered to collect the solid product, and purified by recrystallization to obtain pure 5-aminobenzotriazole.
[0030] The voltage of the anodization is 40V, the temperature is 25°C, and the time is 20min.
[0031] After grinding, cleaning and chemical polishing, the thickness of the titanium sheet or titanium alloy sheet is 1-3 mm. The graphite electrode is used as the cathode, and the two electrodes are immersed in the same fluorine-free electrolyte.
[0032] The cleaning is carried out by using ultrapure water, acetone and ethanol in sequence under ultrasonic conditions for 10 minutes respectively.
[0033] The current density of the chemical polishing is 35A / dm 2 , polishing time 10min.
[0034] The chemical polishing solution comprises, by parts by mass: 300 parts of anhydrous ethanol; Malic acid 400 parts; 300 parts of tartaric acid; Perchloric acid 50 parts; Perchlorate 10 parts.
[0035] The perchlorate is ammonium perchlorate.
[0036] Example 2 A method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy, the method comprising the following steps: Using a titanium sheet or titanium alloy sheet that has been polished, cleaned, and chemically polished as an anode, anodizing is performed in a fluorine-free electrolyte, and the anodized titanium dioxide nanotubes are rinsed 2-3 times with deionized water, and dried in air to obtain a finished product with titanium dioxide nanotubes grown on the surface of the titanium sheet or titanium alloy sheet; The fluorine-free electrolyte comprises phosphoric acid, a surfactant, a solvent, a film-forming additive, a corrosion inhibitor and deionized water. The mass parts of each component in the electrolyte are: 1 part of phosphoric acid, 2 parts of surfactant, 50 parts of solvent, 1 part of film-forming additive, 3 parts of corrosion inhibitor and 50 parts of deionized water.
[0037] The surfactant is sodium dodecylbenzene sulfonate.
[0038] The film-forming additive is vinylene carbonate.
[0039] The solvent is ethylene glycol.
[0040] The corrosion inhibitor is 5-aminobenzotriazole and imidazole, and the mass ratio of 5-aminobenzotriazole to imidazole is 4:1; The voltage of the anodization is 50 V, the temperature is 15° C., and the time is 40 min.
[0041] After grinding, cleaning and chemical polishing, the thickness of the titanium sheet or titanium alloy sheet is 1-3 mm. The graphite electrode is used as the cathode, and the two electrodes are immersed in the same fluorine-free electrolyte.
[0042] The cleaning is carried out by using ultrapure water, acetone and ethanol in sequence under ultrasonic conditions for 15 minutes respectively.
[0043] The current density of the chemical polishing is 15A / dm 2 , polishing time 20min.
[0044] The chemical polishing solution comprises, by parts by mass: 400 parts of anhydrous ethanol; Malic acid 200 parts; 400 parts of tartaric acid; 150 parts of perchloric acid; 1 part perchlorate.
[0045] The perchlorate is sodium perchlorate.
[0046] Example 3 A method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy, the method comprising the following steps: Using a titanium sheet or titanium alloy sheet that has been polished, cleaned, and chemically polished as an anode, anodizing is performed in a fluorine-free electrolyte, and the anodized titanium dioxide nanotubes are rinsed 2-3 times with deionized water, and dried in air to obtain a finished product with titanium dioxide nanotubes grown on the surface of the titanium sheet or titanium alloy sheet; The fluorine-free electrolyte comprises phosphoric acid, a surfactant, a solvent, a film-forming additive, a corrosion inhibitor and deionized water. The mass parts of each component in the electrolyte are: 3 parts of phosphoric acid, 1 part of surfactant, 60 parts of solvent, 1.5 parts of film-forming additive, 4 parts of corrosion inhibitor and 40 parts of deionized water.
[0047] The surfactant is sodium dodecylbenzene sulfonate.
[0048] The film-forming additive is vinylene carbonate.
[0049] The solvent is glycerol.
[0050] The corrosion inhibitor is 5-aminobenzotriazole and imidazole, and the mass ratio of 5-aminobenzotriazole to imidazole is 5:1; The voltage of the anodization is 70V, the temperature is 25°C, and the time is 10 minutes.
[0051] After grinding, cleaning and chemical polishing, the thickness of the titanium sheet or titanium alloy sheet is 1-3 mm. The graphite electrode is used as the cathode, and the two electrodes are immersed in the same fluorine-free electrolyte.
[0052] The cleaning is carried out by using ultrapure water, acetone and ethanol in sequence under ultrasonic conditions for 20 minutes respectively.
[0053] The current density of the chemical polishing is 20A / dm 2 , polishing time 5min.
[0054] The chemical polishing solution comprises, by parts by mass: 600 parts of anhydrous ethanol; Malic acid 300 parts; 200 parts of tartaric acid; 300 parts of perchloric acid; 5 parts of perchlorate.
[0055] The perchlorate is potassium perchlorate.
[0056] Comparative Example 1 The difference between this comparative example and Example 1 is: The dosage of surfactant is 0.5 parts
[0057] Comparative Example 2 The difference between this comparative example and Example 1 is: The surfactant is fatty alcohol polyoxyethylene ether.
[0058] Comparative Example 3 The difference between this comparative example and Example 1 is: The amount of the film-forming additive is 0.5 parts.
[0059] Comparative Example 4 The difference between this comparative example and Example 1 is: The film-forming additive is propylene glycol methyl ether.
[0060] Comparative Example 5 The difference between this comparative example and Example 1 is: The voltage of the anodic oxidation is 30V.
[0061] Comparative Example 6 The difference between this comparative example and Example 1 is: The voltage of the anodic oxidation is 80V.
[0062] The microscopic morphologies of the titanium dioxide nanotubes prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The specific results are shown in Table 1.
[0063] Table 1 Performance test results
[0064] It can be seen from the above performance test results that the pore sizes of Examples 1-3 are relatively stable and are neatly perpendicular to the substrate surface, especially Example 1 has the most outstanding comprehensive performance. This is mainly because by adjusting the composition of the electrolyte, the defects of titanium dioxide nanotubes in electrochemical applications can be effectively overcome, and the verticality can be significantly improved by setting the parameters of anodization.
[0065] However, the comparative examples did not adopt the necessary technical solutions, resulting in the corresponding performance tests being significantly worse than those of the embodiments. In comparative examples 1 and 2, the amount and type of surfactants were changed, and it can be seen that defects appeared on the surface, proving that surfactants have an important influence on surface defects. In comparative examples 3 and 4, the amount and type of film-forming additives were changed, and it can be seen that defects appeared on the surface, proving that film-forming additives have an important influence on surface defects. In comparative examples 1 and 2, the voltage was changed, and the voltage had a significant effect on the pore size. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0066] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy, characterized in that: The method comprises the following steps: Using a titanium sheet or titanium alloy sheet that has been polished, cleaned, and chemically polished as an anode, anodizing is performed in a fluorine-free electrolyte, and the anodized titanium dioxide nanotubes are rinsed 2-3 times with deionized water, and dried in air to obtain a finished product with titanium dioxide nanotubes grown on the surface of the titanium sheet or titanium alloy sheet; The fluorine-free electrolyte comprises phosphoric acid, a surfactant, a solvent, a film-forming additive, a corrosion inhibitor and deionized water. In parts by mass, the mass parts of each component in the electrolyte are: 1-5 parts of phosphoric acid, 1-2 parts of surfactant, 40-60 parts of solvent, 1-2 parts of film-forming additive, 2-4 parts of corrosion inhibitor and 40-50 parts of deionized water.
2. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: The surfactant is sodium dodecylbenzene sulfonate, and the solvent is ethylene glycol or glycerol.
3. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: The film-forming additive is vinylene carbonate.
4. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: The corrosion inhibitor is 5-aminobenzotriazole and imidazole, and the mass ratio of 5-aminobenzotriazole to imidazole is 3-5:1; The preparation method of the 5-aminobenzotriazole comprises the following steps: Step 1: Synthesis of 5-nitrobenzotriazole In an ice bath, concentrated sulfuric acid is cooled to 0°C; under continuous stirring, concentrated nitric acid is slowly added to the concentrated sulfuric acid, the temperature is controlled not to exceed 10°C, and pre-cooled benzotriazole is slowly added to the mixed acid, while maintaining the reaction temperature at 10°C; the mixture is stirred at low temperature for nitration reaction, and 5-nitrobenzotriazole is obtained after neutralization and washing; Step 2: Reduction of 5-nitrobenzotriazole to obtain 5-aminobenzotriazole The 5-nitrobenzotriazole obtained in the first step is dissolved in water and heated to 50° C. Under continuous stirring, a reducing agent hydrazine hydrate solution is slowly added dropwise, the temperature is maintained at 80° C., and the addition is completed within 0.3 hours. After the addition is completed, the reaction is continued at the same temperature for 1-3 hours, the reaction mixture is cooled to 40° C., and then filtered to collect the solid product, and purified by recrystallization to obtain pure 5-aminobenzotriazole.
5. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: The voltage of the anodization is 40-70V, the temperature is 15-25°C, and the time is 10-40min.
6. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: After grinding, cleaning and chemical polishing, the thickness of the titanium sheet or titanium alloy sheet is 1-3 mm. The graphite electrode is used as the cathode, and the two electrodes are immersed in the same fluorine-free electrolyte.
7. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: The cleaning is carried out by using ultrapure water, acetone and ethanol in sequence under ultrasonic conditions for 10-20 minutes respectively.
8. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: The current density of the chemical polishing is 15-35A / dm 2 , polishing time 5-20min.
9. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 1, characterized in that: The chemical polishing solution comprises, by parts by mass: 300-600 parts of anhydrous ethanol; Malic acid 200-400 parts; Tartaric acid 200-400 parts; Perchloric acid 50-300 parts; Perchlorate 1-10 parts.
10. The method for preparing titanium dioxide nanotubes on the surface of titanium or titanium alloy according to claim 9, characterized in that: The perchlorate is one of ammonium perchlorate, sodium perchlorate and potassium perchlorate.
